2012
DOI: 10.1080/03088839.2012.671544
|View full text |Cite
|
Sign up to set email alerts
|

Price formation of dry bulk carriers in the Chinese shipbuilding industry

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Mulligan (2008) presented a simple econometric model to estimate the newbuilding vessel cost in the dry bulk market. Jiang and Lauridsen (2012) employed component principal analysis to solve the multi-collinearity and indicated that the time charter rate has the most significant positive impact on Chinese newbuilding ship price. Some other unique ''China Factors'' were identified to explain the results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mulligan (2008) presented a simple econometric model to estimate the newbuilding vessel cost in the dry bulk market. Jiang and Lauridsen (2012) employed component principal analysis to solve the multi-collinearity and indicated that the time charter rate has the most significant positive impact on Chinese newbuilding ship price. Some other unique ''China Factors'' were identified to explain the results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies on ship price just mainly focus on modeling the level of ship prices (both newbuilding and secondhand), such as Charemza and Gronicki (1981), Beenstock and Vergottis (1989), Stopford (1988), Lun and Quaddus (2009), Tsolakis et al (2003), and Jiang and Lauridsen (2012). Some have paid attention to the volatile characteristics of secondhand price in bulk markets, Kavussanos (1997) realized the uncertainty in secondhand vessel price played an important role in asset management and investment decision-making.…”
Section: Introductionmentioning
confidence: 98%
“…The contracting activity of new ships as well as the prices of new buildings indicate the state of the shipbuilding industry [12]. Although the prices of new ships differ with regard to various factors, Clarkson's Index indicates the total price movement of the new buildings with upward trend [16].…”
Section: The World's Shipbuilding and Newbuilding Pricesmentioning
confidence: 99%
“…His main conclusion is that if the shipbuilding in a country is largely navy related, the impact of the crisis is reduced. Jiang and Lauridsen (2012) focused on the price forming of yards and its dependence on the time charter (TC) rates; other variables are cost price, capacity and profit margin. Pruyn (2013) also showed that price is mostly dependant on TC rates, and used proxies for cost price, capacity and size.…”
Section: The 2009 Crisis In Shippingmentioning
confidence: 99%